2017
DOI: 10.1140/epjb/e2017-80370-6
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous dispersion in correlated porous media: a coupled continuous time random walk approach

Abstract: We study the causes of anomalous dispersion in Darcy-scale porous media characterized by spatially heterogeneous hydraulic properties. Spatial variability in hydraulic conductivity leads to spatial variability in the flow properties through Darcy's law and thus impacts on solute and particle transport. We consider purely advective transport in heterogeneity scenarios characterized by broad distributions of heterogeneity length scales and point values. Particle transport is characterized in terms of the stochas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 87 publications
2
28
0
Order By: Relevance
“…Meyer and Tchelepi (2010) have shown that the evolution of Lagrangian velocities may also be modeled as a Markov process in time whose evolution follows a nonlinear Langevin equation. The CTRW and TDRW frameworks model non-Fickian solute transport through broad distributions of independent advective transition times over given length scales intrinsic to the medium structure (Berkowitz & Scher, 1997;Comolli & Dentz, 2017;Painter & Cvetkovic, 2005). In this sense, these approaches assume that particle velocities form Markov processes when sampled equidistantly along trajectories (Benke & Painter, 2003;Cvetkovic et al, 1996;Fiori et al, 2006;Le Borgne et al, 2007, 2008a, this means at time points that are spaced by the advective transition time over a given distance (Cvetkovic et al, 1996;Le Borgne et al, 2007).…”
Section: 1029/2018wr023810mentioning
confidence: 99%
“…Meyer and Tchelepi (2010) have shown that the evolution of Lagrangian velocities may also be modeled as a Markov process in time whose evolution follows a nonlinear Langevin equation. The CTRW and TDRW frameworks model non-Fickian solute transport through broad distributions of independent advective transition times over given length scales intrinsic to the medium structure (Berkowitz & Scher, 1997;Comolli & Dentz, 2017;Painter & Cvetkovic, 2005). In this sense, these approaches assume that particle velocities form Markov processes when sampled equidistantly along trajectories (Benke & Painter, 2003;Cvetkovic et al, 1996;Fiori et al, 2006;Le Borgne et al, 2007, 2008a, this means at time points that are spaced by the advective transition time over a given distance (Cvetkovic et al, 1996;Le Borgne et al, 2007).…”
Section: 1029/2018wr023810mentioning
confidence: 99%
“…Under ergodic conditions, this means for a sufficiently large injection volume and flow domain, the steady space Lagrangian PDF pfalse(vfalse)=limtruep^false(v,false) and the Eulerian velocity PDFs are related through flux‐weighting as shown in (Comolli & Dentz, ; Dentz et al, ; Kang et al, ): pfalse(vfalse)=vpefalse(vfalse)ve. …”
Section: Flow and Transport Behaviormentioning
confidence: 99%
“…Continuous time random walk (CTRW) and time domain random walk models (Berkowitz et al, 2006;Noetinger et al, 2016) provide natural frameworks to upscale transport in media with spatially variable flow properties (Berkowitz & Scher, 1997;Comolli & Dentz, 2017;Dentz et al, 2016;Painter & Cvetkovic, 2005;Puyguiraud et al, 2019b). In these approaches, a solute plume is conceptualized as an assembly of idealized solute particles who transition through time and space by sampling the local flow velocities.…”
Section: Introductionmentioning
confidence: 99%